пусть существует число XY
9 > X > 0
9 > Y >= 0
X - Y = 2
X² + Y² = 52
X = Y + 2
(Y + 2)² + Y² = 52
Y² + 4Y + 4 + Y² = 52
Y² + 2Y - 24 = 0
D = 4 + 96 = 100
Y12 = (-2 +- 10)/2 = -6 4
Y = -4 < 0 нет
Y = 4
X = 6
XY = 64
и наоборот
Y - X = 2
X = 4
Y = 6
числа 64 и 46
пусть существует число XY
9 > X > 0
9 > Y >= 0
X - Y = 2
X² + Y² = 52
X = Y + 2
(Y + 2)² + Y² = 52
Y² + 4Y + 4 + Y² = 52
Y² + 2Y - 24 = 0
D = 4 + 96 = 100
Y12 = (-2 +- 10)/2 = -6 4
Y = -4 < 0 нет
Y = 4
X = 6
XY = 64
и наоборот
Y - X = 2
X² + Y² = 52
X = 4
Y = 6
числа 64 и 46